(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2022)
The philosopher Norberto Bobbio was an important exponent of Italian liberalism and exerted considerable influence on Italian political thought of the second half of the twentieth century. The article examines the few texts by Bobbio relating to cinema. These are three essays published between 1961 and 1962 concerning censorship, freedom of art and eroticism. In these essays Bobbio expresses an opinion contrary to censorship but he critically judges the spread of eroticism in cinema and literature. He therefore calls for an evolution of customs capable of setting limits on erotic excesses. The underestimation of rules – also noted by other commentators in references to other areas of his thought – is a weakness in Bobbio’s reflection of censorship